Concentration of Population on the Territory of Physic-Geographical Rayons of the Chernivtsi Oblast - Volodymyr Krul; Alina Diachuk (Kazimierz Wielki University, 2020)
Concentrations of total and rural population within the limits of 24 physic-geographical rayons (PhGR) through 2001-2016 have been counted. Seven intervals (optimal, moderate, sufficient and excessive concentration, and moderate, sufficient and excessive sparseness) of concentration of total and rural population were suggested. Synchronic, diachronic and rating analyses of territorial specificities of the values of population's concentration in natural regions of the Chernivtsi Oblast were conducted. Regions of excessive and insufficient concentrations of total and rural population within the Prut-Dniester Elevated Plain Oblast, the Prut-Siret Elevated Oblast, and the Skybovi Carpathians have been established.